PARTISIPASI MASYARAKAT DALAM PELESTARIAN HUTAN MANGROVE DI KELURAHAN OESAPA BARAT KOTA KUPANG - Fransisca Xaveriana Serafina Lio; Stefanus Stanis (Jurnal Kawistara, 2017)
One of the districts in East Nusa Tenggara that has mangrove forests along the coastline is Kupang City, particularly West Oesapa region. Based on the result of preliminary observation, mangrove forest has been used as a recreational area. On the other hand, the partially of mangrove forest area has been earmarked for aquaculture area and it is an early indication of mangrove forest damage. In order to ensure the sustainability, the conservation efforts are needed which couldn’t be separated from community participation. Therefore, the need for a study about the community participation degree in conserving mangrove forest. A total of 30 respondents are interviewed using a questionnaire, taken by purposive. In-depth interviews are conducted to 5 villagers as key informants. Data include socioeconomic conditions, knowledge, perception, and community participation on mangrove forest. Data are analyzed by crosstab to examine the relationship between knowledge and perception, knowledge and participation, and perception and participation. The research result shows that the community knowledge about the benefits of mangrove forests is high, which is 68%. Knowledge of damage is low, which is 74%, but the knowledge of damage prevention is high, which is 77%. The community perception of benefits, damages and prevention is high at 68%, 55% and 49%. Community participation in training of the important existence and mangrove forest utilization is low, which is 65%, and 61%, while participation in the prevention of damage is high, which is 49%.